Programming in the OSEK/VDX environment - Lemieux, Joseph (CMP Books, 2001)
Achieve efficiencies in programming your embedded communications and control systems by using the OSEK/VDX open standard. Developed by the automotive industry to increase productivity through the use of a standard architectural system and re-useable code, Use the OSEK/VDX open standard to program embedded computer control systems. Each of the three OSEK/VDX standards are presented independently so you can refer to the sections pertinent to your project. Features an example application that demonstrates all aspects of the standard without focusing on its automotive origins.